Topographic memory and Victorian travellers in the Dolomite Mountains : peaks of Venice - Bainbridge, William (Amsterdam : Amsterdam University Press, 2020)
Guided by the romantic compass of Byron, Ruskin, and Turner, Victorian travellers to the Dolomites sketched in the mountainous backdrop of Venice a cultural 'Petit Tour' of global significance. As they zigzagged across a debatable land between Italy and Austria, Victorians discovered a unique geography characterized by untrodden peaks and unfrequented valleys. The discovery of this landscape blended aesthetic, scientific, and cultural values utterly different from those engendered by the bombastic conquests of the Western Alps achieved during the 'Golden Age of Mountaineering'. Filtered through memories of the Venetian Grand Tour, their encounter with the Dolomites is revealed through a series of distinct cultural practices that paradigmatically define a 'Silver Age of Mountaineering'. These practices reveal a range of geographic concerns that are more ethnographic than imperialistic, more feminine than masculine, more artistic than sportive - rather than racing to summits, the Silver Age is about rambling, rather than conquering peaks, it is about sketching them in a fully articulated interaction with the Dolomite landscape.
Introduction: Tools for Unravelling Heritage -- 1 The Alps and the Grand Tour -- 2 The Laboratory of the Picturesque -- 3 The Golden Age of Mountaineering -- 4 The Silver Age of Mountaineering -- 5 Titian Country -- 6 Picturesque Mountains -- 7 Dolomite Close-Ups -- 8 King Laurin's Garden -- Epilogue: Messner Country -- Bibliography -- Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed July 15, 2020).
JSTOR
Keywords: Dolomite Alps (Italy) -- Description and travel; Venice (Italy) -- Description and travel; Dolomite Alps (Italy) -- History -- 19th century; British -- Travel -- Italy -- History -- 19th century; Dolomites (Italie) -- Descriptions et voyages; Venise (Italie) -- Descriptions et voyages; Dolomites (Italie) -- Histoire -- 19e siècle.; Britanniques -- Voyages -- Italie -- Histoire -- 19e siècle.; European history; Social and cultural history; Travel and holiday; LITERARY CRITICISM -- Subjects & Themes -- Nature; British -- Travel; Travel; Travelers' writings, English; Italy; Italy -- Dolomite Alps; Italy -- Venice; 1800-1899; Alps; Dolomites; Landscape; heritage; landscape art; nineteenth century; travel writing; History; Criticism, interpretation, etc